Optimizing E-Government Cybersecurity through Artificial Intelligence Integration - Jha, Rahul Kumar; Jha, Mona (Journal of Trends in Computer Science and Smart Technology, 2024)
This study explores the integration of Artificial Intelligence (AI) into e-governance cybersecurity, focusing on its key insights, contributions, challenges, and future directions. AI-powered cybersecurity systems offer advanced capabilities in threat detection, response, and scalability, improving the protection of critical infrastructure and sensitive data in government digital services. However, ethical considerations such as transparency, fairness, and accountability, as well as challenges related to algorithm biases, data privacy, and cybersecurity skills gap, must be addressed to ensure responsible and effective use of AI technologies. Recommendations for policymakers, government agencies, and researchers are provided to maximize the benefits of AI while mitigating potential risks and enhancing e-governance cybersecurity resilience in the digital age.